(untitled) (Research, Society and Development, 2021)
This article presents an application of the SERVQUAL tool adapted to evaluate the service quality provided in an interstate passenger transport company in the state of Minas Gerais. The research sought to identify which factors influence the quality evaluation of service provided to passengers and, for this purpose, the characteristics valued by passengers were evaluated. The study has an applied, exploratory and descriptive nature, being classified as a quantitative work, as it used statistical models to explain the data obtained. This study demonstrated that the adaptation of SERVQUAL scale, with its five original dimensions, presented four factors, in sequence, which influence the quality service provided: assurance and reliability, tangibility, empathy and responsiveness. The study will enable the organization to establish actions in its strategic planning considering the results and the new scenario environment facing the pandemic.